MANAGEMENT OF CONTRAST ABDOMEN CT SCAN EXAMINATION TECHNIQUES WITH SIQMOID COLON TUMOR CLINICAL AT PRIMA HOSPITAL PEKANBARU - Sonalia meirani saputri; Hasyim Asy’ari (Medical Imaging and Radiation Protection Research Journal, 2025)
Sigmoid colon tumor is one of the malignant diseases of the large intestine that requires high-accuracy imaging examinations to establish the diagnosis, determine the location of the lesion, evaluate the extent of disease spread, and assist in treatment planning. Contrast-enhanced abdominal Computed Tomography (CT) is a widely used imaging modality because it provides detailed visualization of abdominal anatomy. In patients with a clinical diagnosis of sigmoid colon tumor, contrast-enhanced abdominal CT is performed using intravenous contrast media combined with rectal (anal) contrast administration to achieve adequate colonic distension, thereby enabling optimal visualization of the lesion margins. This study aimed to describe the management technique of contrast-enhanced abdominal CT examinations in patients with a clinical diagnosis of sigmoid colon tumor at Prima Hospital Pekanbaru. This study employed a qualitative descriptive research design using a case study approach. Data were collected through direct observation of the examination procedure, interviews with radiographers and radiologists, and documentation review of the Standard Operating Procedures (SOPs) implemented in the radiology department. The examination protocol included patient preparation, laboratory assessment of blood urea and serum creatinine levels to evaluate renal function before intravenous contrast administration, intravenous catheter placement, rectal contrast administration to distend the colonic lumen, followed by intravenous contrast injection using a power injector according to the established examination protocol. Subsequently, CT scanning was performed using optimized scanning parameters to obtain high-quality diagnostic abdominal images. The results showed that the combination of rectal and intravenous contrast media improved visualization of the colonic lumen, enhanced delineation of the tumor margins, and facilitated the assessment of tumor infiltration into adjacent tissues as well as the detection of possible metastases. Appropriate patient preparation, pre-examination renal function assessment, and adherence to the standardized examination protocol were essential factors in producing optimal diagnostic image quality. Therefore, the management of contrast-enhanced abdominal CT examinations for patients with sigmoid colon tumor at Prima Hospital Pekanbaru was performed in accordance with the established procedures, providing comprehensive diagnostic information to support accurate diagnosis and appropriate treatment planning.